Expert Judgements of Integrated Cyberpragmatics Learning Model with Socio-Semiotics Multimodality-Based Cybertext Contexts - R. Kunjana Rahardi; Winci Firdaus (Balai Bahasa Provinsi Bali, 2023)
This research is driven by an increasingly urgent requirement to fuse cyberpragmatics instruction with research findings on cyber texts within a multimodal environment, particularly in the ongoing postCovid-19 pandemic era. The challenge presented by this research problem is addressed through a combination of qualitative and quantitative methodologies. The research framework adopted is the Research & Development model proposed by Borg & Gall. The results indicate that 7.69% of participants found it appropriate for use without any changes, 92.30% found it suitable for use with revisions based on notes, and 0% of participants deemed it unsuitable for use. Thus, it can be inferred that all participants unanimously agreed that the book product of the cyberpragmatics learning model, combined with research on cybertext context, is suitable for use with revisions based on notes. This research has yielded foundational insights into the viability of employing cyberpragmatics learning models as a result of applied research. AbstrakPenelitian ini didorong oleh kebutuhan yang semakin mendesak untuk memadukan pengajaran cyberpragmatics dengan temuan penelitian mengenai teks siber dalam lingkungan multimoda, khususnya di era pandemi pasca-Covid-19 yang sedang berlangsung. Tantangan yang dihadirkan oleh masalah penelitian ini di atasi melalui kombinasi metodologi kualitatif dan kuantitatif. Kerangka penelitian yang diadopsi adalah model Research & Development yang dikemukakan oleh Borg & Gall. Hasil dari penelitian menunjukkan bahwa 7,69% peserta merasa layak digunakan tanpa ada perubahan, 92,30% merasa layak digunakan dengan revisi berdasarkan catatan, dan 0% peserta menilai tidak layak pakai. Dengan demikian, dapat disimpulkan bahwa seluruh peserta sepakat bahwa produk buku model pembelajaran cyberpragmatics yang dipadukan dengan penelitian konteks cybertext layak digunakan dengan revisi berdasarkan catatan. Penelitian ini telah menghasilkan wawasan mendasar mengenai kelayakan penggunaan model pembelajaran cyberpragmatics sebagai hasil penelitian terapan.